Down to Earth: Contextualizing the Anthropocene. (July 2016) - Biermann, Frank; Bai, Xuemei; Bondre, Ninad; Broadgate, Wendy; Arthur Chen, Chen-Tung; Dube, Opha Pauline; Erisman, Jan Willem; Glaser, Marion; van der Hel, Sandra; Lemos, Maria Carmen; Seitzinger, Sybil; Seto, Karen C.
Highlights: The Anthropocene concept risks being framed in a way that is too 'global' and monolithic. The notion of the Anthropocene needs to be scaled down in order to have societal and policy relevance. We synthesize multiple strands of research to add to a more nuanced understanding of the Anthropocene. We provide a more context-dependent, localized and social understanding of the Anthropocene. Abstract: The 'Anthropocene' is now being used as a conceptual frame by different communities and in a variety of contexts to understand the evolving human–environment relationship. However, as we argue in this paper, the notion of an Anthropos, or 'humanity', as global, unified 'geological force' threatens to mask the diversity and differences in the actual conditions and impacts of humankind, and does not do justice to the diversity of local and regional contexts. For this reason, we interpret in this article the notion of an Anthropocene in a more context-dependent, localized and social understanding. We do this through illustrating examples from four issue domains, selected for their variation in terms of spatial and temporal scale, systems of governance and functional interdependencies: nitrogen cycle distortion (in particular as it relates to food security); ocean acidification; urbanization; and wildfires. Based on this analysis, we systematically address the consequences of the lens of the Anthropocene for the governance of social-ecological systems, focusing on the multi-level, functional and sectoral organization of governance, and possible redefinitions of governance systems and policy domains. We conclude that the notion of the Anthropocene, once seen in light of social inequalities and regional differences, allows for novel analysis of issue-based problems in the context of a global understanding, in both academic and political terms. This makes it a useful concept to help leverage and (re-)focus our efforts in a more innovative and effective way to transition towards sustainability.